Australian elite athlete development: An organisational perspective - Sotiriadou, K.; Shilbury, D. (Sport Management Review, 2009)
The purpose of this paper is to examine and map the process of Australian elite athlete development from an organisational perspective, that of 35 national sporting organisations (NSOs). Research on elite development has focused on the significance of economic and cultural factors (macro-level studies) and the role of sport science and athletes` close environment (micro-level studies) in fostering success. In an effort to depict elite athlete development processes in a more inclusive way, this paper offers an evaluation of the ways elite athletes are nurtured from an Australian NSOs perspective adopting a meso-level approach (e.g., programs). The study is based on a document analysis examining 74 annual reports from 35 NSOs over a period of four years, before and after the Sydney Olympic Games and offers a generic framework of the Australian elite athlete development process. The resulting framework shows that various interested groups are involved with nurturing elite athletes through either initiating or implementing specially designed programs or other strategies that cultivate success, and helps broaden the definition of elite development. The implications of successful elite athlete development include increased finances and public profile for sports as well as the creation of pathways to increase interest in sport.